Endogenous Stimuli-Responsive DNA Nanostructures Toward Cancer Theranostics - Hu, Xiaoxue; Xu, Ziqi; Min, Qianhao; Teng, Chao; Tian, Ye (Frontiers in Nanotechnology, 2020)
Nanostructures specifically responsive to endogenous biomolecules hold great potential in accurate diagnosis and precision therapy of cancers. In the pool of nanostructures with responsiveness to unique triggers, nanomaterials derived from DNA self-assembly have drawn particular attention due to their intrinsic biocompatibility and structural programmability, enabling the selective bioimaging, and site-specific drug delivery in cancer cells and tumor tissues. In this mini review, we summarize the most recent advances in the development of endogenous stimuli-responsive DNA nanostructures featured with precise self-assembly, targeted delivery, and controlled drug release for cancer theranostics. This mini review briefly discusses the diverse dynamic DNA nanostructures aiming at bioimaging and biomedicine, including DNA self-assembling materials, DNA origami structures, DNA hydrogels, etc. We then elaborate the working principles of DNA nanostructures activated by biomarkers (e.g., miRNA, mRNA, and proteins) in tumor cells and microenvironments of tumor tissue (e.g., pH, ATP, and redox gradient). Subsequently, applications of the endogenous stimuli-responsive DNA nanostructures in biological imaging probes for detecting cancer hallmarks as well as intelligent carriers for drug release in vivo are discussed. In the end, we highlight the current challenges of DNA nanotechnology and the further development of this promising research direction.